The Effect of Corporate Governance and Income Tax on Income Smoothing - Palupi, Agustin (EQUITY, 2020)
The purpose of this research is to obtain empirical evidence about the factors that influence income smoothing. This research used non-financial companies listed on the Indonesia Stock Exchange from 2015-2017. There are 50 companies that meet the criteria using purposive sampling method. The research model used was regression binary logistic . The results of the research show that leverage,  firm value, profitability firm size, income tax, and dividend payout ratio have an influence on income smoothing. However, managerial ownership and quality audit have no influence on income smoothing. Implication of the research indicate that investors assess income smooting by income tax and accounting numbers in their annual reports for their investment decision.